2017
DOI: 10.1002/adsu.201700121
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated Cellulose‐Based Electrolyte and Electrode for Paper‐Based Supercapacitors

Abstract: Solar photovoltaic technologies could fully deploy and impact the energy conversion systems in our society if mass‐produced energy‐storage solutions exist. A supercapacitor can regulate the fluctuations on the electrical grid on short time scales. Their mass‐implementation requires the use of abundant materials, biological and organic synthetic materials are attractive because of atomic element abundancy and low‐temperature synthetic processes. Nanofibrillated cellulose (NFC) coming from the forest industry is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Nanocellulose provides a 3D porous structure incorporated with carbon nanofibers and LiFePO 4 that can maintain an excellent cycling capacity (85%) even after 1000 cycles [132]. Another recent study used nanocellulose-modified polyethylene separators in the lithium battery to improve the cycling stability of a high-energy density lithium battery [133]. The nanofiber layer is thermally stable and flexible with hydrophilic property; it was coated with polyethylene on both sides to fabricate a novel trilayer separator that significantly enhanced the cycling stability and safety of the lithium battery [133].…”
Section: Applications Of Nanocellulose-based Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocellulose provides a 3D porous structure incorporated with carbon nanofibers and LiFePO 4 that can maintain an excellent cycling capacity (85%) even after 1000 cycles [132]. Another recent study used nanocellulose-modified polyethylene separators in the lithium battery to improve the cycling stability of a high-energy density lithium battery [133]. The nanofiber layer is thermally stable and flexible with hydrophilic property; it was coated with polyethylene on both sides to fabricate a novel trilayer separator that significantly enhanced the cycling stability and safety of the lithium battery [133].…”
Section: Applications Of Nanocellulose-based Electronic Devicesmentioning
confidence: 99%
“…Another recent study used nanocellulose-modified polyethylene separators in the lithium battery to improve the cycling stability of a high-energy density lithium battery [133]. The nanofiber layer is thermally stable and flexible with hydrophilic property; it was coated with polyethylene on both sides to fabricate a novel trilayer separator that significantly enhanced the cycling stability and safety of the lithium battery [133]. Those recent studies showed that nanocellulose-based batteries have great potential to replace the conventional ones and solve the stability and safety concerns of lithium batteries.…”
Section: Applications Of Nanocellulose-based Electronic Devicesmentioning
confidence: 99%
“…In previous reports, we have presented a conductive paper that we refer to as “power paper” ( Figure a). The “power paper” is based on PEDOT:PSS composited with cellulose nanofibrils (CNF), and has been explored as the electrodes in symmetric pseudocapacitor devices . The CNF provides a mechanically robust nanoporous network onto which the conductive polymer self‐organizes to form a conductive cladding layer, as was shown from atomic force microscopy (AFM), grazing incidence wide‐angle x‐ray scattering (GIWAXS), and X‐ray photoelectron spectroscopy (XPS) .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of oxygen-containing functional groups on nanocellulose make them easier to decorate with electroactive materials and to modify the physicochemical properties [34,35,36,37,38,39]. Therefore, nanocellulose-based composite aerogel represents a versatile matrix to prepare lightweight hybrid materials [40,41,42,43,44]. Yang et al have integrated spherical manganese dioxide nanoparticles and other kinds of active nanomaterials with the cellulose nanocrystal (a type of nanocellulose) aerogels, and lightweight, highly porous, and flexible hybrid aerogels for the development of supercapacitor materials [45].…”
Section: Introductionmentioning
confidence: 99%